No Child Left Behind: A postmortem for Illinois - Harman, Wm. Gregory; Boden, Camille; Karpenski, Jeremy; Muchowicz, Nicole (Education Policy Analysis Archives, 2016)
In this study, the outcomes of No Child Left Behind (NCLB), as implemented in Illinois, are evaluated in terms of high school standards testing results between 2003-2013. NCLB was a policy dedicated to closing the gap in schooling outcomes nationally in the space of a decade. There have been few systematic examinations of its macro-level results for those exiting high school, especially considering the attention, time, effort, and money dedicated to its implementation. It has been subsumed into newer reform policies that move forward from the same assumptions and structures without a look back. This is a macro study of the outcomes in one state, Illinois, using its assessment system. Data include Prairie State Achievement Examination (PSAE) results in reading and math as well as graduation rates from high schools. The data is evaluated across the state as a whole and within categories of urban, suburban, town, and rural. Outcomes in reading, math, and graduation rates remain unchanged across the decade at the state and all community-type categories. Potential problems with implementation and design of NCLB are proposed with the intention of informing current and future policy, especially in regard to continuing a standards/accountability regime under the Common Core.